ANALISIS TINGKAT REDAM BUNYI DARI BEBERAPA JENIS BAHAN AKUSTIK KAIN PERCA - Husna, Afifah; Daulay, Zubair Aman; Daulay, Abdul Halim (UIN Sumatera Utara Medan, 2023)
Research was carried out on the analysis of the sound absorption level of several types of patchwork acoustic materials which aims to find out whether patchwork can be used as a sound dampening material, to determine the sound absorption level of several types of patchwork acoustic materials and to determine the best attenuation level of several types of patchwork acoustic materials. the type of patchwork acoustic material. The background of this research is due to the acoustic quality of the room which has received less attention for the comfort of listeners when they are in a room. The study used variations of sound absorbing materials, namely cotton and denim patchwork. Measurement of the sound absorption coefficient of patchwork is done by making a sample chamber with a length of 13.5 cm, a width of 13.5 cm and a height of 8.5 cm. Sound Level Meter is a tool used to measure the level of sound pressure. Variations in the thickness of the patchwork used were 3, 5, and 10 mm. In measuring the entire inner wall surface of the sample room will be covered with patchwork, then the speaker is placed in the sample room. The sound source comes from speakers with a frequency of 90 dB which is arranged in a frequency range of 125, 250, 500, 1000, 2000 and 4000 Hz. The best damping level of the three materials is a mixture of cotton and denim with a thickness of 10 mm, because the thicker the patchwork layer, the α value obtained is 0.629.